(untitled) (Research, Society and Development, 2021)
COVID-19 is a communicable disease caused by the SARS-CoV-2 virus, which emerged in December 2019, in China. Such a pathogen has spread across the globe in an uncontrolled manner, culminating in a pandemic that has been causing disastrous impacts. In most deaths from COVID-19, hypertension, obesity, diabetes mellitus, heart disease, and respiratory conditions, such as tuberculosis, were present. Tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis, and is a major public health problem worldwide due to its wide geographic dispersion, cases of multidrug resistance, and because it is a relevant factor for morbidity and mortality. In addition, its main characteristic is pulmonary involvement, which is of great concern when associated with cases of COVID-19. The objective of this work is to systematize information, critically contextualizing the central issue about the COVID-19/tuberculosis interaction, seeking to analyze evidence described on the subject with emphasis on its direct and indirect impacts. To this end, an integrative literature review was conducted, outlined by searching for bibliographies and scientific articles in the main electronic repositories. The descriptors used were: tuberculosis, COVID-19, impact, coinfection, history, epidemiology, risk factors, diagnosis, vaccine, and clinical/laboratory changes. Finally, we note that the COVID-19/tuberculosis interaction is associated with unfavorable and lethal outcomes for patients, as well as indirect impacts. Therefore, new strategies for the control/management of both diseases are of great urgency. However, knowledge on the subject is still limited, with the need for further studies on the possible variables and effects still unknown.